The impact of digital inclusive finance on rural income growth in China: evidence from quantile regression approach - Tang, Caihong; Mao, Yunyi; Rosland, Anitha; Yasmeen, Rizwana (Routledge, 2024)
Based on a panel data set from 2013 to 2021 of Chinese provinces and regions, this research aims to reveal the impact of digital inclusive finance on rural disposable income in China. The linear regression approach with Driscoll-Kraay standard errors and the quantile regression approach are applied in this research. Both approaches show that digital inclusive finance significantly impacts China’s rural income growth. The regression results of China’s east, middle and west area separately imply that the impact of digital inclusive finance in on rural disposable income is higher in the east area and middle area than that in the west area. The quantile regression results show that the impact in the higher quantile is larger than in the lower quantile, which indicates rural high-income groups get more benefits from digital inclusive finance than rural low-income groups. Moreover, this research finds that the development of e-commerce contributes significantly to rural disposable income growth. The empirical results of this research indicate that the establishment of digital inclusive finance in the west backward area still need to be improved to increase the access of digital inclusive finance for rural low-income groups. © 2024 Informa UK Limited, trading as Taylor & Francis Group.